Production and Immunological Characterization of scFv Specific to Epitope of Opisthorchis viverrini Rhophilin-Associated Tail Protein 1-like (OvROPN1L) - Amornrat Geadkaew-Krenc; Dawid Krenc; Jeeraphong Thanongsaksrikul; Rudi Grams; Wansika Phadungsil; Kittirat Glab-ampai; Pathanin Chantree; Pongsakorn Martviset (Tropical Medicine and Infectious Disease, 2023)
(1) Background: Opisthorchis viverrini is a significant health problem in the Mekong subregion of Southeast Asia, causing aggressive cholangiocarcinoma. Current diagnostic procedures do not cover early diagnosis and low infection. Hence, an effective diagnostic tool is still required. Immunodiagnosis seems promising, but attempts to generate monoclonal antibodies have not yet been successful. This study aims to develop a single-chain variable antibody fragment (scFv) against Rhophilin-associated tail protein 1-like (ROPN1L), the sperm-specific antigen of adult O. viverrini, which has not been reported elsewhere. (2) Methods: The target epitope for phage screening was L3-Q13 of OvROPN1L, which showed the highest antigenicity to human opisthorchiasis analyzed in a previous study. This peptide was commercially synthesized and used for phage library screening. The isolated phage was produced in a bacterial expression system and tested for specificity in vitro and in silico. (3) Results: One of fourteen phages, named scFv anti-OvROPN1L-CL19, significantly bound to rOvROPN1L compared with non-infected hamster fecal extracts. This phage clone was successfully produced and purified using Ni-NTA chromatography. Indirect ELISA demonstrated that scFv anti-OvROPN1L-CL19 has a high reactivity with O. viverrini-infected hamster fecal extracts (12 wpi, n = 6) in comparison with non-infected hamster fecal extracts (0 wpi, n = 6), while the polyclonal rOvROPN1L antibodies did not show such a difference. Molecular modeling and docking confirmed our in vitro findings. (4) Conclusion: scFv anti-OvROPN1L-CL19 could be used as an effective material for developing O. viverrini-immunodiagnostic procedures in the future.